Meso-tetra(4-sulfonatophenyl)porphyrin silver/Ag nanoparticles/graphene-phase C3N4 with a sandwich-like structure and double-faced active centers via two-step room-temperature photocatalytic synthesis for ractopamine detection. Issue 13 (28th May 2021) - Weng, Xuehua; Ye, Huiling; Xie, Wenqiang; Ying, Meihui; Pan, Haibo; Du, Min
Abstract : Ag2 TPPS4 /AgNPs/ng-C3 N4 with a sandwich structure was synthesized via two-step photocatalytic synthesis, and the composite with double-faced active sites and a conductor (AgNPs) was applied to the electrochemical detection of ractopamine. Abstract : Photochemical synthesis under visible light irradiation is a novel approach in the field of green chemistry, and composites with abundant active centers for electrochemical detection are highly attractive. Herein, a meso-tetra(4-sulfonatophenyl)porphyrin silver/Ag nanoparticles/graphene phase C3 N4 nanosheets (Ag2 TPPS4 /AgNPs/ng-C3 N4 ) material with a sandwich-like structure was synthesized using a two-step photocatalytic reaction at room temperature (25 °C). In the first visible light irradiation step and in the presence of a hole capture agent, Ag + ions were photocatalytically reduced onto the surface of ng-C3 N4 that was used as a photocatalyst. Then, the protons (H + ) in the core of H2 TPPS4 were substituted in situ by photo-oxidized Ag + during the second visible light irradiation step and in the presence of an electron capture agent. The electrochemical response of Ag2 TPPS4 and ng-C3 N4 to ractopamine (RAC) results in the unique double-faced active centers of Ag2 TPPS4 /AgNPs/ng-C3 N4, and the cores (AgNPs) are beneficial as bridges for the connection between Ag2 TPPS4 and ng-C3 N4 and for high-efficiency electron transfer. Hence, as-synthesized Ag2 TPPS4 /AgNPs/ng-C3 N4 exhibits high sensitivity (a low detection limit of 5.1 × 10 −8 M, S/N = 3.0), a wide linear range (1 × 10 −7 to 1.2 × 10 −5 M), and long-term stability. Based on the experimental verification of the electrochemical dynamics and electrostatic attraction at the interface between the dual-active-center surface and RAC, the electrochemical mechanism has been clarified. Specifically, in the multi-cycle oxidation of RAC, the blue shift of specific UV-vis peaks also confirms the electrocatalytic oxidation of the two terminal hydroxyl groups of RAC. In brief, Ag2 TPPS4 /AgNPs/ng-C3 N4 with a sandwich-like structure and double-faced active centers enhances the detection sensitivity and electrocatalytic efficiency towards RAC.